Isolation and selection of cellulose-chitosan degrading bacteria to speed up the mineralization of bio-based mulch films - Sidari, Rossana; Pittarello, Marco; Rodinò, Maria Teresa; Panuccio, Maria Rosaria; Lo Verde, Gabriella; Laudicina, Vito Armando; Gelsomino, Antonio (Frontiers in Microbiology, 2025)
IntroductionMulching is a common agricultural practice owing to its advantages during cultivation. To reduce plastic residues in soil, the use of biodegradable films instead of plastic is desirable. Once buried in soil, biodegradable films undergo degradation driven by abiotic and biotic factors such as the activity of soil microbes. The aim of this study was to select microbial strains whose enzymatic activities can accelerate the degradation of innovative, biodegradable, cellulose-chitosan-based films.MethodsTo this end, 119 bacteria were isolated from compost, digestate, agricultural soil, and the gut or casts of earthworms and subsequently tested for their ability to break down two types of biodegradable films, which were enriched with nitrogen and phosphorus (+NP) and the unenriched control (-NP).Results and discussionThe ability of the bacteria to accelerate the degradation of the films was strain dependent, and the degradation proceeded at different speeds and degrees. Of the 119 isolated bacteria, 46 strains were able to degrade the unenriched (-NP) film to a greater or lesser extent, with 20 of them able to break it down completely. With regard to the enriched (+NP) film, 10 strains were able to degrade it, with six strains being able to break it down completely. These figures include eight strains that were able to degrade both the enriched and unenriched films. Four novel cellulose-chitosan-degrading bacteria were selected and identified as Bacillus subtilis ACT-8, Bacillus spp. DL-A1-11, Pseudomonas spp. I1, and Staphylococcus warneri F7. These strains will be further studied to assess their activity in a mesocosm-scale trial. The novelty of this study is the identification of bacterial strains capable of degrading cellulose-chitosan-based films. This finding contributes to the common effort to reduce the presence of axenic residues in the environment and may have a positive impact on the sector, considering the possibility of applying these strains in bioaugmentation.